2021
DOI: 10.1002/lary.29623
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postoperative Facial Palsy for Benign Parotid Tumors: Outcome of 1,018 Patients

Abstract: The aim of this study was to evaluate the rate of postoperative facial palsy in benign parotid tumors, as well as its risk factors, pathology, and clinical results.Study Design: Retrospective analysis.Methods: We performed a retrospective analysis of data from patients whose initial operation for a benign parotid tumor had been performed in our department between 1999 and 2020.Results: We included 1,018 patients in this study. The most common tumor observed was pleomorphic adenoma (614 patients), followed by W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The goal of surgical management of benign parotid tumors is to completely remove the tumor and preserve the facial nerve ( 6 ). Partial superficial parotidectomy was characterized by the preservation of part of the unaffected parotid tissue and the dissection of a smaller area of facial nerve branches ( 6 ). Partial superficial parotidectomy was associated with fewer complications and lower recurrence rates than superficial parotidectomy ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of surgical management of benign parotid tumors is to completely remove the tumor and preserve the facial nerve ( 6 ). Partial superficial parotidectomy was characterized by the preservation of part of the unaffected parotid tissue and the dissection of a smaller area of facial nerve branches ( 6 ). Partial superficial parotidectomy was associated with fewer complications and lower recurrence rates than superficial parotidectomy ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, recurrence after partial superficial parotidectomy was observed in only 1 patient (2%) with pleomorphic adenoma. Even if the facial nerve is completely preserved, a certain rate of postoperative facial nerve palsy is inevitable ( 6 ). The incidence of transient facial nerve palsy after parotidectomy for benign parotid tumors ranges from 10–65%, with persistent palsy seen in <5% of cases ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article "Risk Factors of Postoperative Facial Palsy for Benign Parotid Tumors: Outcome of 1,018 Patients" by Ryo Kawata et al with great interest and would like to congratulate the authors on their excellent work in attempting to highlight the possible risk factors for facial palsy after parotid surgery for benign tumors. 1 However, there are a few questions that we would like to have clarified in order to gain a better understanding of the study.…”
mentioning
confidence: 99%
“…This study investigated patients who underwent partial parotidectomy. 1 In most patients, the facial nerve is identified by anterograde approach (AA). In rare cases, a tumor is located just above the superficial layer of the main trunk is dissected the facial nerve by retrograde approach (RA).…”
mentioning
confidence: 99%